KEPEMIMPINAN INOVATIF KEPALA MADRASAH DALAM PENINGKATAN MUTU MADRASAH - Vionita Ayulistiani; Agus Timan; Imron Arifin; Mustiningsih Mustiningsih; Vionita Ayulistiani; Agus Timan; Imron Arifin (Universitas Negeri Malang, 2024)
Abstract: This study aims to identify and describe the innovative leadership of madrasah principals in improving the quality of madrasahs. This study uses a qualitative method with the type of case study research. This research was conducted at MIN 1 Malang City. Data were collected using interview techniques, observation, and documentation. Then analyzed through an interactive process through the stages of reduction, presentation, and verification of data. The results of this study are: (1) the characteristics of the headmaster's innovative leadership in improving the quality of madrasah; (2) the innovative leadership role of madrasah principals in improving the quality of madrasahs; (3) innovative leadership strategies of madrasah principals in improving the quality of madrasahs; (4) indicators of quality improvement of innovative leadership; (5) problematic implementation of the principal's innovative leadership and solutions